2012
DOI: 10.1183/09031936.00186911
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae-induced regulation of cyclooxygenase-2 in human lung tissue

Abstract: The majority of cases of community-acquired pneumonia are caused by Streptococcus pneumoniae and most studies on pneumococcal host interaction are based on cell culture or animal experiments. Thus, little is known about infections in human lung tissue.Cyclooxygenase-2 and its metabolites play an important regulatory role in lung inflammation. Therefore, we established a pneumococcal infection model on human lung tissue demonstrating mitogen-activated protein kinase (MAPK)-dependent induction of cyclooxygenase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 39 publications
3
54
0
Order By: Relevance
“…The prominent role of pneumococcal DNA and TLR9 for KLF4 induction is shown by experiments using purified pneumococcal DNA, CpG DNA, siRNA based silencing of TLR9 and TLR9 inhibiting oligonucleotides as well as LytA-deficient pneumococci unable to liberate DNA (6). The activity of LytA degrades the pneumococcal cell wall, resulting in the lysis of the bacteria and thereby the liberation of pneumococcal cell wall components that are able to activate, e.g., TLR2.…”
Section: Discussionmentioning
confidence: 98%
“…The prominent role of pneumococcal DNA and TLR9 for KLF4 induction is shown by experiments using purified pneumococcal DNA, CpG DNA, siRNA based silencing of TLR9 and TLR9 inhibiting oligonucleotides as well as LytA-deficient pneumococci unable to liberate DNA (6). The activity of LytA degrades the pneumococcal cell wall, resulting in the lysis of the bacteria and thereby the liberation of pneumococcal cell wall components that are able to activate, e.g., TLR2.…”
Section: Discussionmentioning
confidence: 98%
“…While these studies advance our understanding of neutrophil recruitment and killing, experimental depletion of neutrophils in murine pneumococcal pneumonia models has previously revealed serotype-specific effects ranging from deleterious to a beneficial effect on lethality [8183]. In another recent study, pro-inflammatory responses to pneumococcus were modulated by MAPK-dependent induction of COX-2 in response to pneumococcal pneumonia, leading to prostaglandin release [84], revealing a novel mechanism by which the inflammatory consequences of neutrophil killing are modulated.…”
Section: The Role Of Host Inflammation In Pneumococcal Pneumoniamentioning
confidence: 99%
“…The earlier presence of surfactant in female neonatal lungs helps open the small airways and may contribute to their higher airflow rate observed [50]. Evidence from human studies suggests that male infants are more susceptible to lung infection, with greater associated morbidity and mortality than female infants, but the reverse is applied in children and adolescents [47,51,52]. Regarding respiratory tract infections (RTIs), women are more 3.…”
Section: Gender Differences In Community-acquired Pneumoniamentioning
confidence: 99%
“…that is also highly expressed in mouse and human lungs after infection is prostaglandin E (PGE 2 ), and its precursor enzyme cyclooxygenase-2 (COX2) [52]. Studies using depletion of alveolar macrophages have demonstrated that these contribute largely to the stimulation of pro-inflammatory cytokines, such as IL-6 and TNFα [48].…”
Section: Strain Differences and Associated Mechanismsmentioning
confidence: 99%